Are demographics, work and health associated with the ability and motivation to continue working until the age of 65 in construction workers?. (19th October 2011) - Hengel, Karen Oude; Blatter, Birgitte; Geuskens, Goedele; Koppes, Lando; Bongers, Paulien
Abstract : Objectives: Because of the ageing and decreasing working population in the construction industry, it is important to encourage workers to prolong their working life. The objective of this study was to explore factors associated with the ability and motivation to continue working until the age of 65 years in construction workers. Methods: In total 5610 construction workers that participated in the Netherlands Working Conditions Surveys of 2007, 2008 and 2009 were included. Workers filled out questionnaires on demographic, work-related and health-related factors, and the ability and motivation to continue working. Logistic regression analyses were applied. Results: Higher job tenure, lower supervisory support, and musculoskeletal complaints were significantly associated with both a lower ability and motivation to continue working, whereas overtime work was associated both with a higher ability and motivation. In addition, frequently using force, working in awkward postures, lower job autonomy and emotional exhaustion were associated with a lower ability to continue working, whereas older age and intermediate emotional jobs demands were associated with a higher ability. Furthermore, a low educational level was associated with a lower motivation to continue working, and having a partner without a paid job was associated with a higher motivation. Conclusions: Supervisory support and preventing musculoskeletal complaints are promising to prolong workforce participation in the construction industry as they support both the ability and motivation to continue working. Moreover, reducing physical job demands, increasing job autonomy, and preventing emotional exhaustion are relevant for the ability to continue working.